Dietary Sugar and Ischaemic Heart Disease. Issue 5663 (19th July 1969) - Howell, R. W.; Wilson, D. G.
Abstract : Comparison of the sugar intake of 1, 158 men believed to be free of ischaemic heart disease failed to establish any real difference in intake when compared with 170 men with confirmed or possible ischaemic heart disease. In neither group was mere any significant correlation between sugar intake and serum cholesterol, white blood cell count, haemoglobin, E.S.R., β-lipoprotein, or uric add; nor was there any correlation between total sugar intake and weight gain after the age of 25 years. These results suggest that considerably more confirmation is required before acceptance of Yudkm's hypothesis that high sugar intake is the chief dietary factor causing ischaemic heart disease.